2021
DOI: 10.1088/1755-1315/640/2/022030
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value of persimmon, banana, lemon and longan cultivated in Northern Vietnam

Abstract: An analysis of nutritional composition of some common fruits (persimmon, banana, lemon, longan) grown in Northern Vietnam was conducted. These fruits, at their ripening stage, showed distinctive flavors and colors and contain a high content of nutrients. They owned relatively high content of vitamins, protein, lipid and reducing sugar, and also contained essential amino acids mostly including glutamic acid, aspartic acid, leucine. Additionally, the mineral content in the fruits also achieved a high level, main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Additionally, in case of Grape fruit the tannin content decreased from 4.45 to 3.50, which might be attributed to the dilution effect [59]. Similar observation might be expected in case of Assam lemons [60].…”
Section: Tanninssupporting
confidence: 74%
“…Additionally, in case of Grape fruit the tannin content decreased from 4.45 to 3.50, which might be attributed to the dilution effect [59]. Similar observation might be expected in case of Assam lemons [60].…”
Section: Tanninssupporting
confidence: 74%
“…From the Table 6, it can be concluded that yogurt with the addition of a higher concentration of banana puree produced a higher total LAB. Banana contains many sources of nutrients needed for the growth of lactic acid bacteria including various types of amino acids, the most dominant are lysine (1.16%), glutamic acid (1.1%), tryptophan (0.92%), and leucine (0.72%), as well as fatty acids including palmitic fatty acid (74.33-95.45 mg/100g), linoleic acid (22.39-55.14 mg/100g), and linolenic acid (23.53-42.22 mg/100g) [35,36]. In addition, the presence of prebiotic can also increase the growth of LAB.…”
Section: Total Lactic Acid Bacteriamentioning
confidence: 99%
“…Although the main substrate utilized by lactic acid bacteria is lactose, but sucrose can also act as a source of energy for LAB in metabolism [42]. Bananas also contain various nutrients such as fatty acids and amino acids which are a source of nutrition for lactic acid bacteria [35,36]. The presence of inulin in bananas also contributes to increasing the activity of lactic acid bacteria so that more acid was produced and results in a decrease in the pH of the yogurt.…”
Section: Phmentioning
confidence: 99%
“…The fruit industry in Vietnam has expanded in recent years, yet its performance in both foreign and domestic markets has not developed proportionately [1] [2]. This is due to weaknesses in postharvest handling practices and ineffective sales system [3] [4].…”
Section: Introductionmentioning
confidence: 99%